Does variety matters for therapeutic application of Ficus Deltoidea Jack? - Khamsah Suryati, Mohd (2014)
Proper identification of the plant source with related biological property is fundamental in herbal standardisation. Ficus deltoidea Jack (FD), a South East Asian native plant, 1s traditionally used to treat several diseases and pharmacologically tested to posses several biological activities. However, there is confusion on the identification of plant material as FD occurs as at least in eight varieties, namely Ficus deltoidea var. deltoidea, var. trengganuensis, var. kunstleri, var. motleyana, var. intermedia, var. bornensis, var. bilobata and var. angustifolia. Since reports on pharmacological and chemical studies are not at the varietal level, it is difficult to identify the best variety to be commercia lised. In order to characterize the differences between varieties in terms of chemical profiles, eight varieties of FD were collected from several localities around the Malaysian Peninsular and Borneo, and subjected to HPTLC and FTIR fi ngerprinting analysis. The C-linked flavone glycosides, vitexin and isovitexin served as markers. HPTLC chromatograms indicated differences in chemical profile among varieties. Quantitative HPTLC-densitometric showed that FD var. deltoidea contained the highest amount of vitexin ( 15.64 ng/μg, R2=0.990) and FD var. bornensis possesed the most amount of isovitexin (11.73 ng/µg,R2=0.960). Analysis on unsupervised FTIR data using principal component analysis (PCA) found that all eight varieties clustered into eight different groups, where PC 1 showed 86%, are near to the axis of the origin indicating that they were from the same species but differed at some point between varieties. Based of HPTLC-densitometric quantification and chemometric analysis of FTIR spectra, chemical composition of F deltoidea varieties was significantly different from each other. Findings from this study will assist the selection of the best variety to be developed further as herbal medicines.